Physical education, exercise, and sport science in a changing society - Freeman, William Hardin, 1943- (Jones & Bartlett Learning, 2011)
Physical Education, Exercise And Sport Science In A Changing Society, Seventh Edition Provides A Current, Complete, And Balanced Introduction To The Fields Of Physical Education, Sport, And Exercise Science. It Gives A Thorough Overview Of The Varied Elements Within The Disciplines, How They Came To Be, And How They Are Developing, Including The Conflicts Over Field, Major, And Departmental Names. It Also Examines The Developing Sub-Disciplines Within Physical Education, Sport, Exercise Science, And Kinesiology. The Seventh Edition Has Been Thoroughly Revised And Updated To Represent The State And Potential Of The Field Of Physical Education Today. It Surveys Both Teaching And Non-Teaching Careers And Addresses Technology, Current Issues, And Future Trends. Instructor Resources: Powerpoint Presentations, Instructor S Manual, Testbank